Financial Performance Analysis at PT. Inka Multi Solusi Consulting - Ningsih, Astuti; Sahabuddin, Romansyah; Ramli, Anwar; Burhanuddin, Burhanuddin; Hamka, Rezky Amalia (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
This research aims to assess the financial performance of the company using financial ratio analysis at PT. INKA Multi Solusi Consulting for the period 2017-2021. This research is of a quantitative descriptive type. Data analysis is carried out using financial ratio analysis, including liquidity ratios (current ratio and cash ratio), solvency ratios (debt to asset ratio and debt to equity ratio), activity ratios (fixed asset turnover and total asset turnover), and profitability ratios (return on asset and return on equity). The results of this study indicate that the financial performance of the company, as measured by the liquidity ratios, shows favorable outcomes based on the current ratio in 2020 and 2021, despite unfavorable results based on the cash ratio. Furthermore, when assessing solvency ratios using the (DAR) and (DER), the results are favorable..However, the activity ratio measured by total asset turnover is consistently decreasing, placing the company in the less favorable category. On the other hand, fixed asset turnover is in the good category. However, the financial performance for profitability ratios with return on asset and return on equity indicators indicates less favorable results